Atopic Dermatitis Treatments Before and After Initiation of Ruxolitinib Cream: 6-Month Follow-Up Analysis of a US Payer Claims Database - Liu J; Desai K; Teng CC; Sturm D; Stockbower G; Patadia H; Willey V (ClinicoEconomics and Outcomes Research)
Jinan Liu,1 Karishma Desai,2 Chia-Chen Teng,2 Daniel Sturm,1 Grace Stockbower,2 Hiten Patadia,1 Vincent Willey2 1Incyte Corporation, Wilmington, DE, USA; 2Carelon Research, Inc., Wilmington, DE, USACorrespondence: Jinan Liu, Incyte Corporation, 1801 Augustine Cut-Off, Wilmington, DE, 19803, USA, Tel +1 504 810 7282, Email jinliu@incyte.comPurpose: Many patients with atopic dermatitis (AD), a highly pruritic, relapsing, inflammatory skin disease, experience inadequate disease control. Ruxolitinib cream was approved in the US in September 2021 for the treatment of mild-to-moderate AD. This analysis describes treatment patterns before and after initiation of ruxolitinib cream among patients with AD.Patients and Methods: This retrospective, observational study used medical and pharmacy claims data from the Healthcare Integrated Research Database (HIRD®) and included adults and adolescents (aged ≥ 12 years) with an AD diagnosis, a first claim for ruxolitinib cream (index date) between October 2021 and July 2022, and continuous enrollment in a commercial or managed Medicare plan for 6 months before and after the index date. Analyses were also conducted in a subset of patients with a history of more advanced AD therapy (ie, systemic therapies, phototherapy, or ultrahigh-potent topical corticosteroids). Data from 6 months before ruxolitinib cream initiation (baseline period) and after initiation (follow-up period) were summarized using descriptive statistics.Results: Of 1,581 patients in the overall AD cohort, 749 had a history of more advanced AD therapy. During the follow-up period, 43.8% of patients did not receive any other AD treatment. Compared with baseline, fewer patients received topical corticosteroids (52.3% vs 30.4%), topical calcineurin inhibitors (13.9% vs 6.6%), and topical phosphodiesterase-4 inhibitors (4.4% vs 2.3%) during the follow-up period; slightly greater reductions were observed among the subset with a history of more advanced AD therapies. Oral corticosteroid use decreased from 20.9% to 15.5% overall and from 44.1% to 20.7% in the subset with more advanced baseline therapy. Among patients receiving biologics at baseline, 17.4% did not receive these treatments during the follow-up period.Conclusion: These 6-month follow-up data suggest that initiating ruxolitinib cream for AD may reduce the overall need for other topical treatments, oral corticosteroids, and biologics.Plain Language Summary: Ruxolitinib cream is a recently approved medicine used to treat atopic dermatitis (AD), a disease that causes itchy and dry skin. It is a topical Janus kinase inhibitor and not a steroid. We wanted to explore how the use of ruxolitinib cream affected the use of other medicines used to treat AD. Using medical and pharmacy insurance records, we found that patients used less of other treatments for AD after starting ruxolitinib cream.Keywords: atopic dermatitis, Janus kinase, ruxolitinib cream, topical